MENGUAK BUDAYA MENJEMPUT LIMAU PADA MASYARAKAT MELAYU KUANTAN MUDIK DALAM CERPEN PERAHU BAGANDUANG KARYA AHMAD IJAZI - Marlina nfm (Balai Bahasa Sumatera Utara, 2019)
Picking up lime by using Perahu Baganduang (joined boats) in the Kuantan Mudik society of Riau was a cultural procession carried out by a a young man to propose a girl whom he loves. Perahu Bagandung means two or three boats are joined to become one by using bamboo. Then it is decorated in such a way with meaningful symbols in Kuantan Mudik Malay society. Ornaments, colourful fabrics, and other decoration make the boat looks pretty and beautiful. Ahmad Ijazis Perahu Baganduang (Joined Boats) short story tells about the unique culture of picking up lime by using the decorative boat. The short story is full of a local Malay culture of Kuantan Mudik. In the course of time, picking up lime by perahu baganduang has become boat race in an event of Perahu Baganduang Festival held annually every Idul Fitri feast. The festival is an effort to conserve a Malay culture that is regarded highly unique. Similarly, Ahmad Ijazis short story is also an effort to conserve Malay culture. The research used descriptive analytical method and socio literary method for the theoretical framework. Picking up lime by Perahu Baganduang in Ahmad Ijazis Perahu Baganduang was a cultural tradition to propose a girl. In the course of time, Perahu baganduang is nevertheless used more frequently in an annual event of boat race in Kuantan Mudik. The cultural shift of picking up lime happens because its procession is considered too complicated and difficult.